Comparison of mobilization with movement and Mulligan knee taping on Patellofemoral pain syndrome - Mubarra Rehman; Huma Riaz (Journal of the Pakistan Medical Association, 2021)
Objective: The objectives of study are to compare Mobilization with Movement (MWM) and Mulligan knee taping (MT) on anterior knee pain, hamstring flexibility and Physical performance of lower limb. Methods: A randomized control trail was conducted from July to Dec 2019. Ethical approval from Riphah research ethical committee was taken. Total 34 participants of both genders, having Patellofemoral pain were recruited by purposive sampling technique. Randomly assignment into two groups; MWM and MT was done. Both groups were treated for 2 days per 2 consecutive weeks. Outcomes measures were Numeric pain rating scale(NPRS), Kujala pain rating scale, Active knee extension test(AKE) and Time up and go test(TUG). Assessment were taken at baseline, 2nd and 6th weeks after treatment. Data analysis was done through SPSS-21 version. Results: Between group analysis has shown statistically significant improvement (p< 0.000) in NPRS and Kujala score in MWM group whereas hamstring flexibility is significant in (p< 0.000) MT group. Within group analysis has shown a statistically significant differences (p< 0.000) for all outcome variable in both groups. Conclusion: It is concluded that Mulligan’s MWM is more effective in treatment of patellofemoral pain and associated knee functional performance. Clinical Trial Number: This clinical trail is prospectively registered at www.ClinicalTrails.gov(NCT04173468) Keywords: Anterior knee Pain. Patellofemoral pain Syndrome, Mobilizations with Movement, Mulligan knee taping, Kujala pain rating scale, Active knee extension test, Continuous....